Inequality across societies families, schools and persisting stratification - Baker, David, 1952 Jan. 5- (Research in sociology of education ;, 2004)
Most societies place great faith in the modern school's power to offer children a more prosperous future, from better jobs to wider social opportunities. In turn, political leaders around the world push to expand western forms of schooling, creating more slots for children, from preschool through university levels. Yet despite this remarkable institutional change, are societies becoming equitable, especially for those groups living on the margins of civil society? Why, in too many cases, has schooling failed to deliver on its promise of reducing economic and social disparities? This volume addresses these questions, taking the reader into a variety of nations and cultural settings. With studies from Europe, the Middle East, Africa, and Asia, the volume illuminates how schools can reduce or reinforce the layered stratification of society, even in nations with non-western traditions. The contributors, diverse in their own origins and viewpoints, advance our understanding of stratification by highlighting how a nation's history, particular institutions, and cultural context shape the school's efficiency as an agent of equity. The chapters move beyond individual conceptions of attainment and distinguish near-universal versus country-specific mechanisms that characterize the interplay between school expansion and inequality. It shows how schools can reduce or reinforce the layered stratification of society, even in nations with non-western traditions.